Effect of Sonication and Nano TiO2 on Thermophysiological Comfort Properties of Woven Fabrics - Noman, Muhammad Tayyab; Petru, Michal (ACS omega, 2020)
The main aim of the present study was to investigate the effects of ultrasonic irradiation on thermophysiological comfort properties of TiO2-coated fabrics. The results were evaluated on the basis of heat and mass transfer as well as air permeability performances. Alambeta, a permetester, an air permeability tester, and a moisture management tester were used for thermal evaluation and air and moisture transportation, respectively. Hundred percent pure cotton and polyester woven fabrics were used for this study. Moreover, the study explains the effect of sonication on surface roughness of textile woven fabrics. TiO2 nanoparticles were deposited onto selected fabrics by sonication. Surface topography, changes regarding surface roughness, and the presence of nano TiO2 were evaluated by scanning electron microscopy (SEM), energy dispersive X-ray (EDX) analysis, X-ray diffractometry (XRD), and inductively coupled plasma atomic emission spectroscopy (ICP-AES). Furthermore, standard test methods were carried out to evaluate physical and overall thermophysiological comfort properties, i.e., thermal conductivity, thermal absorptivity, relative water vapor permeability, absolute evaporative resistance, air permeability, and overall moisture management capacity of TiO2-treated and untreated samples.